Short-term Results of Microendoscopic Muscle-preserving Interlaminar Decompression versus Spinal Process Splitting Laminectomy - Fukushi, Ryunosuke; Yoshimoto, Mitsunori; Iesato, Noriyuki; Terashima, Yoshinori; Takebayashi, Tsuneo; Yamashita, Toshihiko (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Study Design A retrospective comparative study.Objective To compare retrospectively the clinical results and surgical invasiveness of two different types of minimally invasive surgery for lumbar spinal canal stenosis: microendoscopic muscle-preserving interlaminar decompression (ME-MILD) and spinal process splitting laminectomy (SPSL).Summary of Background Data ME-MILD and SPSL are minimally invasive procedures. However, the two procedures have not been compared in the literature.Materials and Methods We retrospectively enrolled patients who underwent ME-MILD or SPSL from 2011 to 2015. The surgical invasiveness of each technique was determined by evaluating the time required for the surgical procedure, amount of blood loss, serum creatine kinase (CK) levels on postoperative day (POD) 1, C-reactive protein (CRP) levels on POD 3 and 7, and the hospitalization. The clinical results were evaluated using the Japanese Orthopaedic Association Back Pain Evaluation Questionnaire score, the Short Form (36) Health Survey patient-reported outcome score, the visual analog scale for pain, a patient satisfaction score, and the incidence of surgical complications.Results A total of 97 patients were evaluated: 58 patients underwent ME-MILD, and 39 patients underwent SPSL. No significant differences were observed in the clinical results between the two groups. Regarding surgical invasiveness, no significant difference was found in the amount of blood loss, levels of CK, hospitalization, or time required for the procedure. However, CRP levels were significantly lower in the ME-MILD group.Conclusions ME-MILD and SPSL are both minimally invasive procedures. In a comparison of these two procedures, CRP was significantly lower in the ME-MILD group.
Keywords: spinal process splitting laminectomy; surgical invasiveness; clinical results; microendoscopic muscle-preserving interlaminar decompression